Size Changes in Differentiating Neuroblastoma Cells - Kisaalita, William S.; Lund, Robert B.; Evans, Mark (In vitro cellular & developmental biology. Animal, 1997)
Day 12 0.0001 0.5572 0.4714 0.0001 0.0005 0.0001 0.0081 0.0001 control reject don't don't reject reject reject reject reject Ho rej. Ho rej. Ho Ho Ho Ho Ho Ho aBlocks below and above the main diagonal compare control vs. control and treatment vs. treatment, respectively, across the day of study. bp-values for Z-test. light scatter (FALS), one of the flow cytometry parameters, is as light of the same wavelength as the illuminating laser bea is refracted as it passes through the cell so as to diverge fr original path of the laser beam by approximately 0.5'. Henc is dependent on both cell refractive index and size. The r distribution of differentiating/differentiated cells between lo high-FALS has been proposed as a potential culture electrop logical differentiation index before and after terminal differe (Kisaalita and Bowen, 1997). Our purpose here is to study t lationship between cell-size distribution and culture age for entiating and control cells, and perhaps more importantly, ass effect of cell differentiation size changes to FALS. How c changes influence FALS has biological relevance when usin as a measure of the extent of electrophysiological differentiat saalita and Bowen, 1997). N1E-115 cells of Passage 12 were obtained from Dr. M. Nire National Institutes of Health (Bethesda, MD). Previously pub protocols for N1E-115 cell cultures (Kimhi et al., 1976; Mo and Spector, 1978; Miyake and Kurihara, 1983) were fol Briefly, N1E-115 cells were routinely cultured in 370 C air p CO2 at 90% relative humidity. The growth media was comp Dulbecco's modified Eagle's medium (DMEM) containing NaHCO3 (wt/vol) and supplemented with 13% fetal bovine (FBS), 50 units/ml penicillin, 50 g/ml streptomycin, and 2 m tamine. Cultures were monodispersed gently by flushing the c ent cells from the base of a 75-cm2 T-flask (Costar, Cambrid by a stream of medium ejected from a Pasteur pipette. The sions were centrifuged (500 g, 10 min) and the pellet resusp in 25-cm2 T-flasks (Costar) with fresh growth media at 2.0 viable cells (able to exclude trypan blue) per flask, unless oth stated. Flasks (in triplicate) were incubated for 24 h to allow to settle and adhere to the base of the flask. Cells were then e to the differentiating medium (this is the same as the growth except serum was reduced to 0.5%). The differentiating medi changed every 3 to 4 d. Cell-size data were taken at Days 1, 6, 8, 10, and 12 after exposure to the differentiating mediu saalita and Bowen (1997) have previously shown that it tak